(untitled) (Andamios, Revista de Investigación Social, 2011)
This article analyzes the processes of implementation of gender equality in International Development Cooperation as an expression of the hidden agenda of coloniality. The hypothesis states that in the background of these processes hides a homogenizer desire by which the goals of the West Society appear as the goals of the world. The aim is to present a general overview of the theoretical discussion based on the review of modern feminist critical theories, postcolonial theories and some discoveries of feminist anthropology. The main findings suggest that the processes of gender equality inclusion in development are surreptitious ways of institutionalize the modern Western feminism principles at the expense of subaltern feminisms.